2020
DOI: 10.3748/wjg.v26.i46.7367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of nonalcoholic fatty liver disease in patients with inflammatory bowel diseases: A cross-sectional and longitudinal analysis

Abstract: BACKGROUND Nonalcoholic fatty liver disease (NAFLD) is common in the German population, with an even higher prevalence in inflammatory bowel disease patients. AIM To investigate the risk factors for NAFLD in inflammatory bowel disease patients. METHODS This monocentric retrospective study with a cross-sectional and a longitudinal part included 694 patients. Inclusion criteria were diagnosed inflammatory bowel disease, age ≥ 18 years, availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 29 publications
(10 reference statements)
1
48
0
Order By: Relevance
“…There were 11 studies reporting the prevalence of NAFLD in IBD patients according to NAFLD severity. 5,19,21,23,26,28,30,35,39,44,57 The pooled prevalence of mild-to-moderate NAFLD was higher than severe NAFLD among patients with IBD (78.7% [95% CI 69.4-88.1] versus 21.3% [95% CI 11.9-30.6]). In patients with CD, the pooled prevalence of mild-to-moderate NAFLD was higher than severe NAFLD (69.7% [95% CI 64.4-74.9] versus 30.3% [95% CI 25.1-35.6]).…”
Section: Pooled Prevalence Of Nafld In Patients With Ibd According To...mentioning
confidence: 99%
See 1 more Smart Citation
“…There were 11 studies reporting the prevalence of NAFLD in IBD patients according to NAFLD severity. 5,19,21,23,26,28,30,35,39,44,57 The pooled prevalence of mild-to-moderate NAFLD was higher than severe NAFLD among patients with IBD (78.7% [95% CI 69.4-88.1] versus 21.3% [95% CI 11.9-30.6]). In patients with CD, the pooled prevalence of mild-to-moderate NAFLD was higher than severe NAFLD (69.7% [95% CI 64.4-74.9] versus 30.3% [95% CI 25.1-35.6]).…”
Section: Pooled Prevalence Of Nafld In Patients With Ibd According To...mentioning
confidence: 99%
“…There were 15 studies that reported the prevalence of NAFLD according to sex. 5,6,13,24,30,31,33,35,[37][38][39]42,48,53,54 Overall, the pooled prevalence was higher in men with IBD (33.2%, 95% CI 25. 1).…”
Section: Pooled Prevalence Of Nafld In Patients With Ibd According To...mentioning
confidence: 99%
“…, steroids, biological agents, immunomodulators, methotrexate) and the risk of developing NAFLD[ 78 ]. Several studies also reported a higher prevalence of NAFLD among IBD patients with severe disease activity at the time of liver evaluation, compared to mild-moderate IBD cases[ 77 , 79 , 80 ].…”
Section: Non-immune-mediated Disordersmentioning
confidence: 99%
“…A recent retrospective study showed that the presence of clinical activity (Harvey Bradshaw Index > 4), history of intestinal resection, endoscopic activity, and the use of AZA would be risk factors with statistical association for NAFLD in patients with CD. In the case of UC, there was an association between NAFLD and endoscopic activity[ 61 ]. MS appears not to be the only triggering factor for NAFLD in patients with IBD.…”
Section: Nafldmentioning
confidence: 99%